Legislações e mapeamento de acessibilidade na cidade de São Paulo por meio de aplicativos digitais e plataformas colaborativas - Leme, Cauê Bettini Paes (2022)
This policy paper aims to suggest the implementation of data collection mechanisms on accessibility conditions of sidewalks in the city of São Paulo. Taking as a model the experience of Project Sidewalk, already active in cities in the U.S. and Mexico, we hope that this initiative can be reproduced in São Paulo and, with the use of voluntary popular participation and artificial intelligence, to collect data that can be used in the creation of public policies that improve the conditions of sidewalks in cities around the world, especially in São Paulo